Variabel Dominan yang Memengaruhi Penggelapan Pajak: Systematic Literature Review - Ekaputra, Aditiyanto; Triyono, Triyono; Ahyani, Fatchan (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2024)
This article aims to determine and analyze the development of publications and the dominant variables that influence tax evasion based on the Google Scholar and Scopus databases. The method used in the article is a literature study approach. Search for journal publication databases on Google Scholar and Scopus using the Publish or Perish program to make it easier to search and filter suitable publications. The three applications used in this article are publish or perish, Mendeley, and VOSviewer. The development of publications that were successfully mapped (accessed March 18 2022) on Google Scholar was 1078 publications and Scopus obtained 200 publications, both data were published over a period of ten years (2012-2022). The results of the literature study show that the parameters of tax fairness, taxation system, religiosity, tax discrimination, love of money, tax sanctions, understanding of taxation, tax tariffs, money ethics, and gender are known to be the dominant variables influencing tax evasion based on the Google Scholar database. Meanwhile, the cultural parameters of corruption, information technology systems, economic growth, financial development, tax audits, political electoral cycles, behavioral economics, law enforcement, fiscal policy and cultural values are the dominant variables influencing tax evasion based on the Scopus database.